Electrical and Optical Properties of Au-Catalyzed GaAs Nanowires Grown on Si (111) Substrate by Molecular Beam Epitaxy - Wang, Chiu-Yen (Nanoscale Res Lett, 2017)
In this study, defect-free zinc blende GaAs nanowires on Si (111) by molecular beam epitaxy (MBE) growth are systematically studied through Au-assisted vapor-liquid-solid (VLS) method. The morphology, density, and crystal structure of GaAs nanowires were investigated as a function of substrate temperature, growth time, and As/Ga flux ratio during MBE growth, as well as the thickness, annealing time, and annealing temperature of Au film using scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), cathodoluminescence (CL), and Raman spectroscopy. When the As/Ga flux ratio is fixed at 25 and the growth temperature at 540 °C, the GaAs nanowires exhibit a defect-free zinc blende structure with uniform and straight morphology. According to the characteristics of GaAs nanowires grown under varied conditions, a growth mechanism for defect-free zinc blende GaAs nanowires via Au-assisted vapor-liquid-solid (VLS) method is proposed. Finally, doping by Si and Be of nanowires is investigated. The results of doping lead to GaAs nanowires processing n-type and p-type semiconductor properties and reduced electrical resistivity. This study of defect-free zinc blende GaAs nanowire growth should be of assistance in further growth and applications studies of complex III-V group nanostructures.